Development of Industrial and Urban Areas in the Context of Ecological and Economic Security - SHAIMERDENOVA, Aigul; TIREUOV, Kanat; KERIMOVA, Ukilyay; MURSALIMOVA, Elmira (Journal of Environmental Management and Tourism, 2020)
The national security of Kazakhstan, considering the current state of the environment, will increasingly depend on the economic condition and ecosystem, as well as effective government management measures. The main causes of the world's environmental problems are associated with the intense development of industrial production, which predetermines the increase in man-made impact on the environment. Most large cities are characterized by the unorganized location of industrial enterprises. The aim of the present study is to identify the prerequisites, to study the characteristics, and develop techniques for restructuring industrial areas of the contemporary city. The article defines at the theoretical level the essence of economic and environmental security, as well as of the restructuring of industrial and urbanized territories. Based on the expert survey, the main factors of restructuring of industrial areas are determined including directions, goals, and objectives of integrated restructuring of industrial areas. Recommendations are given for restructuring of industrial areas with respect to their planning structure, functional organization, andprovision of an ecological condition.